EFFECT OF ELASTIN HEDROLYSES ON THE CHEMICAL COMPOSITION AND SOME OXIDATION INDICATORS IN COLD-STORED GROUND BEEF - Ghufran M.M. Al-ghanimi,; Alrubeii A. M., (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
This study was aimed to investigate the effect of elastin hydrolysates extracted from bovine skin on the chemical composition and some indicators of oxidation in minced beef stored in refrigeration at a temperature of 2 °C for a period of 12 days. The study included 6 treatments T1 (without addition), T2 addition (1000 ppm) of elastin hydrolysates per kg of meat, T3 addition (500 ppm) of elastin hydrolysates per kg of meat, T4 addition (1000 ppm) of collagen hydrolysates per kg of meat, T5 addition (500 ppm) of collagen hydrolysates per kg of meat and T6 addition of the antioxidant BHA (0.01) per kg of meat. the transactions were stored by cold storage for periods 1, 3, 6, 9 and 12 days, and some chemical tests were conducted for them, The results of this study showed that treatments to which elastin hydrolysate was added showed a significant improvement in the chemical composition (moisture, protein, fat and ash) of ground beef stored in cold storage compared to the control treatment. It also showed a significant decrease (P